2013
DOI: 10.1111/ssqu.12011
|View full text |Cite
|
Sign up to set email alerts
|

Show Them the Mission: A Comparison of Teacher Recruitment Incentives in High Need Communities

Abstract: Objective. Most public organizations use both materialistic and idealistic appeals to attract valued employees, with the latter being particularly important for difficult jobs. Teaching in high poverty communities is one such job, though none have studied whether successful high poverty schools such as the Knowledge Is Power Program (KIPP) schools make relatively greater use of public service appeals in teacher recruitment. In education, we identify these materialistic and idealistic appeals as teachercentered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The hiring process at Polaris begins at the network level with CMO-based social media and advertising. Similar to Shuls and Maranto's (2014) and Maranto and Shuls' (2012) findings of KIPP schools, Polaris' advertisements and websites lean heavily upon "student-centered messaging" (e.g., appeals to teamwork, public service, student outcomes/opportunities) more than "teachercentered messaging" (e.g., appeals to salary and benefits) and are more explicit about teacher advancement and professional growth opportunities. Applicants go through a strikingly similar process to the one outlined by Simon et al (2015): an online application, followed by an initial phone screening of fit and credentials with network-level recruitment personnel.…”
Section: Organizational Context: Polaris Academiesmentioning
confidence: 71%
See 1 more Smart Citation
“…The hiring process at Polaris begins at the network level with CMO-based social media and advertising. Similar to Shuls and Maranto's (2014) and Maranto and Shuls' (2012) findings of KIPP schools, Polaris' advertisements and websites lean heavily upon "student-centered messaging" (e.g., appeals to teamwork, public service, student outcomes/opportunities) more than "teachercentered messaging" (e.g., appeals to salary and benefits) and are more explicit about teacher advancement and professional growth opportunities. Applicants go through a strikingly similar process to the one outlined by Simon et al (2015): an online application, followed by an initial phone screening of fit and credentials with network-level recruitment personnel.…”
Section: Organizational Context: Polaris Academiesmentioning
confidence: 71%
“…As mentioned earlier and as is true of numerous CMOs (e.g., DeArmond et al, 2012;Farrell et al, 2012;Shuls & Maranto, 2014;Torres, 2019), Polaris determines and controls much of the functioning, including hiring. The hiring process at Polaris begins at the network level with CMO-based social media and advertising.…”
Section: Organizational Context: Polaris Academiesmentioning
confidence: 81%
“…Given the underrepresentation of educators of color (Taie et al, 2017), especially for Black women in leadership positions (Bailes & Guthery, 2020; Peters, 2019) and in rural areas (Tran & Smith, 2020), it is important we understand what allowed our respondents to disrupt the trend. Although altruism has been found to be a motivating factor for many who enter the education profession (Shuls & Maranto, 2014), it seems to be particularly the case for people in high poverty rural locales (Tran, Hardie, et al, 2020). Our participants spoke of the desire to “give back” to and serve as role models for the Black youth in the community.…”
Section: Discussionmentioning
confidence: 99%
“…If the utility provided by meaningfulness was consistent among employees, then economically challenged and rural communities would have too much demand for educators and healthcare providers. Instead, incentives are offered in the United States (Rosenblatt and Hart 2000) and other countries (e.g., Singh et al 2015) to attract physicals to rural areas, and similarly, incentives are offered to educators to work in economically challenged communities (Shuls and Maranto, 2014). If utility including meaningfulness was constant, then homogeneity would exist for worker benefit preferences, but instead, research has long found that workers in the same industry have different preferences (e.g., Kocher et al 2017;Farber 1978).…”
Section: Marginal Utility and Meaningfulnessmentioning
confidence: 99%